Bogong moths use a stellar compass for long-distance navigation at night - David Dreyer; Andrea Adden; Hui Chen; Barrie Frost; Henrik Mouritsen; Jingjing Xu; Ken Green; Mary Whitehouse; Javaan Chahl; Jesse Wallace; Gao Hu; James Foster; et al. (Nature, 2025)
Abstract Each spring, billions of Bogong moths escape hot conditions across southeast Australia by migrating up to 1,000 km to a place that they have never previously visited—a limited number of cool caves in the Australian Alps, historically used for aestivating over summer 1,2 . At the beginning of autumn, the same individuals make a return migration to their breeding grounds to reproduce and die. Here we show that Bogong moths use the starry night sky as a compass to distinguish between specific geographical directions, thereby navigating in their inherited migratory direction towards their distant goal. By tethering spring and autumn migratory moths in a flight simulator 3–5 , we found that, under naturalistic moonless night skies and in a nulled geomagnetic field (disabling the moth’s known magnetic sense 4 ), moths flew in their seasonally appropriate migratory directions. Visual interneurons in different regions of the moth’s brain responded specifically to rotations of the night sky and were tuned to a common sky orientation, firing maximally when the moth was headed southwards. Our results suggest that Bogong moths use stellar cues and the Earth’s magnetic field to create a robust compass system for long-distance nocturnal navigation towards a specific destination.